Pengaruh Pembelajaran STEM Berbasis Masalah Terhadap Penguasaan Konsep Fisika Peserta Didik - Lalu Haditya Arria Rahmana; Muhammad Zuhdi; Sutrio Sutrio (Department of Physics Education, Universitas Mataram, 2022)
This study aims to determine the effect of problem-based STEM learning on students' mastery of physics concepts. The research method used is quasi-experimental with a nonequivalent control group design. The research was carried out from the third week of March to the second week of April at SMAN 1 Sikur. The population of this research was students of class XI MIPA 2, XI MIPA 3, and XI MIPA 4 for the academic year 2021/2022, with a sampling technique using purposive sampling. This study used two classes, namely the control and experimental groups—the Data collection for mastery of concepts using tests in the form of description questions. The research hypothesis was tested using an independent t-test to analyze the difference in the mean scores of pre-test and post-test in both classes using SPSS 16 software. The independent t-hypothesis test resulted in a sig. (2-tailed) of 0.009, more minor than the significance value. (0.05) so that H_0 is rejected, and it is concluded that there are differences in the mastery of physics concepts due to the application of the problem-based STEM learning model.